STORYTELLING: SUPPORTING PRE-SERVICE TEACHERS’ ENGLISH LANGUAGE PROFICIENCY AT A PRIMARY TEACHER EDUCATION PROGRAM - MUTIARA RAMDAYANTI (LINGUISTICA, 2023)
One of the challenges identified in the performance of TEYL in Indonesia comes from the aspect of pre-service teachers of young learners who lack English proficiency. Utilizing storytelling as a teaching technique, this study explores the phenomenon of the storytelling implementation by pre-service teachers from the Primary Teacher Education Program and how it helps them develop their English language proficiency. In order to answer the research question employed in this study, two types of instruments are collected: an interview with four pre-service teachers and their English lecturer and storytelling performance videos created by four of the pre-service teachers. Believed to provide a more joyful environment in learning the language, the development was sensed in the plan step of storytelling where these four pre-service teachers prepare the story, read and listen to story references, and practice to make instruction targeted for young learners inside the class. From the videos and the interview, it was found how the activity of practice making instructions help them develop their speaking skills, indicating improvement in the use of word choice and the fluency performed once the plan step of storytelling is being experienced. Nevertheless, it was also found how the participants involved in this study experienced challenges in terms of the exploration of writing skills due to the limitation time provided in the Pembelajaran Bahasa Inggris Anak Sekolah Dasar course, resulting them to experienced less development in writing skills during the implementation of storytelling inside the class as a teaching technique.